Assignment maximization - Mustafa Oğuz Afacan; Inácio Guerberoff Lanari Bó; Bertan Turhan (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2018)
We evaluate the goal of maximizing the number of individually rational assignments. We show that it implies incentive, fairness, and implementation impossibilities. Despite that, we present two classes of mechanisms that maximize assignments. The first are Pareto efficient, and undominated - in terms of number of assignments - in equilibrium. The second are fair for unassigned students and assign weakly more students than stable mechanisms in equilibrium. We provide comparisons with well-known mechanisms through computer simulations. Those show that the difference in number of matched agents between the proposed mechanisms and others in the literature is large and significant.
Keywords: D47; C78; D63; 330; market design; matching; maximal matching; fairness; object allocation; school choice